2021
DOI: 10.33153/glr.v19i1.3789
|View full text |Cite
|
Sign up to set email alerts
|

Visualisasi Penelitian Tentang Tembang Macapat dari Tahun 1981 – 2021 : Analisis Bibliometrik

Abstract: The macapat song in Indonesia has been widely studied and has become an interesting topic for international analysis. The purpose of this study is to provide an overview of the extent to which the tembang macapat has been researched and published in reputable international journals. This study analyzes the literature from 1981 to 2021, identifies the publications each year, the number of articles and their authors, the most researched topics, and how interested they are in those topics. The data came from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Macapat song has a special characteristic called Paugeran which has guru gatra, guru lagu, and guru wilangan (Cahyono et al, 2020;Irmade & Winarto, 2021;Wibawa et al, 2022). Guru Gatra is the number of lines in each stanza, Guru Wilangan is the number of syllables in each line, and Guru Lagu is the last vowel in each line of the Macapat song.…”
Section: Introductionmentioning
confidence: 99%
“…Macapat song has a special characteristic called Paugeran which has guru gatra, guru lagu, and guru wilangan (Cahyono et al, 2020;Irmade & Winarto, 2021;Wibawa et al, 2022). Guru Gatra is the number of lines in each stanza, Guru Wilangan is the number of syllables in each line, and Guru Lagu is the last vowel in each line of the Macapat song.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, macapat can be used as a medium for character building (Agus et al, 2021). A bibliometric study of macapat from 1981 to 2021 found that most research is focused on cross-cultural and social change perspectives (Irmade & Winarto, 2021). None of them discuss this Javanese song from the computer science or technological aspect.…”
Section: Introductionmentioning
confidence: 99%